Kinetic analysis of protein activity - Baici, Antonio (Henry Stewart Talks, 2007)
Thermodynamics vs. kinetics, Enzyme catalysis, Conventional and rapid kinetic methods, Equilibrium and steady-state approaches, The phases of an enzymatic reaction, Graphical and statistical analysis, Enzyme inhibition, The importance of kinetics for protein activity
Reviewed at 2015/09/06, Archived at 2023/03/30